A comparative study of typologies for rural areas in Europe - Dimitris Ballas; Thanasis Kalogeresis; Lois Labrianidis (European Regional Science Association (ERSA), 2003)
This paper examines alternative methodologies to build a typology for rural areas in Europe. First, it reviews the methodologies that have traditionally been used to construct area typologies in various contexts. It then uses data for European NUTS3 regions to build a typology for rural areas in Europe, on the basis of their peripherality and rurality. First, an aggregative approach to building typologies is adopted, under which the well-established statistical techniques of principal components analysis and cluster analysis are employed. We then highlight the disadvantages of this approach and we present an alternative disaggregative approach to the construction of typologies for rural areas in Europe. Finally, we discuss the policy implications of our suggested typology.
Keywords: 330